Chapter 5 Adaptability, decarbonisation and accessibility Challenges for integrative transport planning in Dar es Salaam - Appelhans, Nadine (Taylor & Francis, 2021)
This chapter focuses on the status quo of transport for people in relation to integrated planning attempts in the city of Dar es Salaam. With the population increase and urban expansion, the need for transport infrastructure and mobility within Dar es Salaam is continuously growing. To manage transport development under these conditions of rapid urban growth, the Dar es Salaam Master Plan of 1979 was the last official master plan authorised by the Ministry of Lands, Housing and Human Settlements Development and has not been replaced Daladalas, small buses and the even smaller microbuses called vipanya are by far the most common way to travel in Dar es Salaam. The World Bank notes that Dar es Salaam's four primary roads and arterial roads are dominated by public transit and walking. However, walking has not yet been sufficiently considered in transport policies in Dar es Salaam, which - unlike Nairobi - does not have a Non-Motorised Transport Policy to date.